Paving the Way to Industrially Fabricated Disposable and Customizable Surface‐Enhanced Raman Scattering Microfluidic Chips for Diagnostic Applications. Issue 8 (2nd February 2022) - Gutiérrez, Yael; Losurdo, Maria; Prinz, Iris; Prinz, Adrian; Bauer, Georg; Bauer, Maria; Schmidt, Martina M.; Schaller, Thorsten
Abstract : Both surface‐enhanced Raman scattering (SERS) spectroscopy and microfluidics are increasing their presence in industry. The integration of SERS into microfluidic chips is relevant for label‐free biosensing and can expand the function of microfluidics to provide an efficient platform for on‐site biochemical analysis equipped with the powerful sensing capability of SERS. Herein, the design and industry manufacturing of reliable and cost‐effective disposable SERS microfluidic chips using high throughput technologies of injection molding and roll‐to‐roll are demonstrated. The SERS microfluidic chip is made of cyclic olein copolymers and of an ultrathin nanostructured polyethylene terephthalate foil covered by a plasmonic nanostructured Ag film, enabling Raman readout through it. This ultrathin plasmonic Ag‐coated PET layer overcomes the drawbacks of SERS through thick polymeric microfluidic cells, i.e., it avoids strong fluorescence signals interfering with the Raman measurements and avoids high working distances. The achieved SERS enhancement in the range 10 5 –10 6 is demonstrated by probing 100 nl of 1 M rhodamine and of 10 −12  m crystal violet with a  > 90% reproducible signal, with large‐area uniformity on all the SERS area of 20 mm 2 and good stability of the signal over months. Therefore, this approach of SERS microfluidic chips provides an industrially viable customizable and cost‐effective route toward disposable, point‐of‐care diagnostic applications. Abstract : The fabrication at industrial scale of a fully customizable polymeric surface‐enhanced Raman scattering (SERS) microfluidic chip is presented. This process combines injection molding for the fabrication of the flow cell and roll‐to‐roll thin film technology to fabricate the ultrathin silver plasmonic nanopatterned component. This approach of SERS microfluidic chips can provide an industrially viable customizable and cost‐effective route toward disposable, point‐of‐care diagnostic applications.